2013
DOI: 10.1097/brs.0b013e318275ca58
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure to the Surgeon During Percutaneous Endoscopic Lumbar Discectomy

Abstract: Without radiation shielding, a surgeon performing 291 PELDs annually would be exposed to the maximum allowable radiation dose. Given the measurable lifetime radiation hazards to the surgeon, the use of adequate protective equipment is essential to reducing exposure during PELD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 34 publications
3
100
0
2
Order By: Relevance
“…Other studies have addressed spine surgeons' radiation exposure in minimally invasive spine surgeries 2,3,5,7,8,10,12,14,15,18,20,22 and in endoscopic spine surgery. 1 Here we prospectively looked at the exposure of patients to radiation during endoscopic spine surgery. Several interesting conclusions can be drawn from the data collected.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have addressed spine surgeons' radiation exposure in minimally invasive spine surgeries 2,3,5,7,8,10,12,14,15,18,20,22 and in endoscopic spine surgery. 1 Here we prospectively looked at the exposure of patients to radiation during endoscopic spine surgery. Several interesting conclusions can be drawn from the data collected.…”
Section: Discussionmentioning
confidence: 99%
“…A reported disadvantage of MIS techniques is higher radiation exposure to the patient and OR staff [13]. The use of computer assisted fluoroscopy based surgery helps to reduce this radiation exposure and simultaneously might contribute to lower misplacement rates of percutaneously inserted pedicle screws [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…8 Choi et al revealed that improper surgical indications and inappropriate working channel position were the dominant reasons for the surgical failure of PELD. 1 Lee et al demonstrated that the rate of surgical failure following PELD was significantly increased in the high-grade migration group, and the centrally located high-canal compromised herniation showed the highest rate of failure in the non-migrated group. 7 Accurate knowledge of the risk factors of surgical failure following PELD for single-level LDH is crucial for guiding decision-making strategies.…”
Section: Responsementioning
confidence: 99%
“…There is a promising belief that PELD will be an effective alternative to open discectomy and might be the gold standard for symptomatic lumbar disc herniation in the future. Herein, we present a re-analysis of 30 cases extracted from the study by Ahn et al 1 and retrospectively analyze the radiation exposure to the surgeon performing 21 cases of PELD in our center (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation